Verdade e subjetividade: um ensaio sobre a epistemologia genética - Correa, Jane (1989)
At the end of the twentieth century, the speech of post-modernity points out the dis-construction of concepts highly valued by the western thinking, such as truth and subjectivity. The challenge science is now facing is, by means of breaking free from laplacean determinism, to find a new rationale which can convey concepts such as unmeasurability, uncertainty, chance, disorder and unforeseeabliness. In these times of plurality, discontinuity, polimorphy and ecletism, genetic epistemology is a project completely inside modernity. So we can consider Jean Piaget, the great narrator of the western analytical reason in our century. In these times of plurality, discontinuity, polimorphy and ecletism, genetic epistemology is a project completely inside modernity. So we can consider Jean Piaget, the great narrator of the western analytical reason in our century. To make Epistemology scientific was the upmost attempt of Jean Piaget -in his own words, 'an old future ex-philosopher'. He tried to rescue the greek episteme, maintaining its supremacy regarding the doxa. Such an ambitious project would only be reasible for someone who took the scientific knowledge as a synonym of the truth, and took science as his own life.